Filosofi dalam Islamisasi Pembelajaran Fisika - Tebriani, Sylvina (Universitas Islam Negeri Imam Bonjol Padang, 2020)
The fast flow of secularization in the world of education is often an important issue to be aware of in the world of education. The negative side of technological development is related to the degeneration of human morals. The development of science and technology is considered not linear with moral improvement. There is a moral and spiritual crisis in it. This is due to the fact that science tends to see things only from worldly perspectives. Islamization in physics learning is needed to overcome the negative side of the development of science. With Islamization in learning, it is hoped that a process of thinking will be created regarding the relationship between moral and divine science to science. This thinking process is a form of philosophy in education. Philosophy helps everyone understand the moral and normative side of an event that can be related to the teaching material to be explored. With the process of thinking, contemplating, connecting, and drawing correct conclusions about a physical theory, it is hoped that it can help students understand concepts more easily and are easier to remember